Wage Bargains, Threshold Effects, and the Phillips Curve: A Reply - Hamermesh, Daniel S. (Quarterly Journal of Economics, 1972)
Journal Article Wage Bargains, Threshold Effects, and the Phillips Curve: A Reply Get access Daniel S. Hamermesh Daniel S. Hamermesh Princeton University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 86, Issue 2, May 1972, Pages 339–341, https://doi.org/10.2307/1880570 Published: 01 May 1972